Design for aging review : AIA design for aging knowledge community - The American Institute Of Architects; American Institute of Architects Design for Aging Center (Australia : Images Publishing Group, 2014)
This compilation of more than 30 outstanding projects in the areas of assisted living, continuing care retirement communities, and nursing homes represents the best current work designed by architects for the ever-increasing aging population. A dedicated jury of architects and providers of senior housing services selected the diverse range of projects featured in this, the twelfth volume in the successful 'Design for Aging' series. Each project is presented with photographs, detailed plans, and statistics, illuminating the high level of research, planning and community involvement that goes into these advancements in living environments for seniors. This comprehensive review of architectural design trends in aged-care facilities will appeal to aged-care providers, developers, users, and advocates; architects; and interior, landscape, and other design professionals. SELLING POINTS: - A comprehensive review of architectural trends in aged-care facilities. Projects are hand-picked by a jury of members from the American Institute of Architects (AIA) Design for Aging Knowledge Community and LeadingAge - First time inclusion of a new Small Projects category to reflect the realities of the recent economic down - This year's jury included six aging-service professionals to encourage broader and more diversified insights during the evaluation process - Features the results of the DFAR12 Insights Study, providing a comprehensive evaluation of the statistics, patterns, and innovations impacting the senior living industry and design community. The study's findings reflect the changing demands and emerging concepts that are reshaping the senior living industry today 220 col.
Keywords: Architecture Awards; Architecture and Planning; Architecture Human factors